Analisis Tingkat Kepuasan Masyarakat Terhadap Pelayanan Becak Bermotor: Studi Kasus Pasar Sentral Kabupaten Polewali Mandar - Aslan Aslan; Hamka Hamka; Andi Bustan Didi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
One of the modes of transpotation available at the Central Market of Polewali Mandar District is a motorized rickshaw. Motorized becak is a modification of traditional becak with motorized vehicles such as motorcycles. The benefits of this research are for consideration by motorized pedicab drivers in order to improve the quality of service to passengers. The results of the analysis using the help of SPSS version 26 software from 100 questionnaire samples distributed with reference to the three factors in this study, namely service quality, safe and comfortable, and bentor tariffs are able to influence the ups and downs of public satisfaction with motorized rickshaw services by 65.6%. Then in partial testing or t test shows that the service quality variable has a result of 0.974, the safe and comfortable variable is 2.342 and the bentor tariff variable with a result of 6.705. This shows that the bentor tariff variable is the factor that is most able to influence the satisfaction of motorized rickshaw consumers in the Central Market of Polewali Mandar Regency.